Alkaline Treatment of Oil Palm Frond Fibers by Using Extract of Oil Palm EFB Ash for Better Adhesion toward Polymeric Matrix - Warman Fatra; Randi Sanjaya; Zulfansyah Zulfansyah; Hari Rionaldo; Zuchra Helwani (Journal of Engineering and Technological Sciences, 2015)
In Indonesia, 187 million tons of biomass were produced from 8.11 million ha of oil palm plantation in 2009. This massive amount of biomass mainly consists of oil palm fronds (OPF) and oil palm empty fruit bunches (EFB), which are normally categorized as waste. The properties of OPF fibers compared to those of synthetic fibers, such as low density, low cost, less abrasion of equipment, and safer production, makes them an attractive reinforcement for composite materials. In this work, the utilization of oil palm empty fruit bunch ash for OPF fiber-polyester resin composite and the effect of process conditions were studied. Water absorption, tensile and flexural strength were used to characterize the effects of alkaline treatment on modified OPF fibers in polyester resin. The investigation focused on the effect of alkaline treatment time. Treatment temperature and liquid to solid ratio were analyzed using Response Surface Method-Central Composite Design (RSM-CCD). The highest tensile strength (44.87 MPa) was achieved at 12 hours soaking time, at 40°C treatment temperature and 5:1 water to ash ratio. The highest flexural strength (120.50 MPa) was obtained at 1.3 hours soaking time, 4 dissolving ratio and 35°C treatment temperature. The lowest water absorption of composite (3.00%) was achieved at the longest soaking time (14.7 hours), 4 dissolving ratio and 35°C treatment temperature. Variance of soaking time, dissolving ratio and temperature in the alkaline treatment process using extract of oil palm empty fruit bunch ash significantly affected the mechanical and physical properties of the oil palm frond fibers reinforced composite.